THE IMPLEMENTATION OF TEACHING SPEAKING AT PEACE ENGLISH COURSE PARE KEDIRI - Khasanah, Uswatun; Musta'in, Musta'in (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 9 No 2 (2019): LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
In academia, many students are seriously in learning English across the four language skills; listening, speaking, reading and writing. This research is aimed to describe the implementation of teaching speaking at PEACE English course Pare Kediri. Descriptive qualitative was used as the approach to design this research. The object of this research is the implementation of teaching speaking at PEACE. The subjects of this research are the teacher and the students of PEACE. The instruments used of this research are observation, interview, questionnaire, and documentation. The analysis data used as reduction the data, displaying the data and verifying. From the result, it can be concluded that the implementation of teaching speaking at PEACE had been implemented well through the contextual teaching and learning used, followed by  discussion and conversation technique, and the presentation as the technique of evaluation. It was proven also through the studentsâ€™ respond toward the teaching speaking program at PEACE was good and satisfying.